Body of secrets how America's NSA and Britain's GCHQ eavesdrop on the world - Bamford, James (Century, 2001)
The NSA is the largest, most secretive and most powerful intelligence ageny in the world. It dwarfs the CIA in budgets, manpower and influence. Using internal documents and interviews with NSA officials, this text offers details about the workings of the agency. It exposes the role the NSA played in many Soviet bloc Cold War conflicts and discusses its undercover involvement in the Vietnam War. Author, James Bamford, also looks at the technological advances that the NSA have employed since 1985 and brings to light the NSA's network of global surveillance ranging from on-line listening post to intelligence-gathering satellites. Bamford warns that the NSA is a double-edged sword, its eavesdropping offers the potential for tracking down terrorists and uncovering nuclear weapons deals, but it also has the capacity to listen in on global personal communications.